A framework for physical growth and child development - Alderman, Harold; Behrman, Jere R.; Glewwe, Paul (International Food Policy Research Institute, 2015)
It is widely recognized that there is a continuum of physical growth and social-emotional and cognitive development across the life course, from the preconception health status of the mother through adulthood. This paper lays out a core economic model that illustrates the interrelationship of investments over the life cycle. It then shows how this framework can be used to the relative cost-effectiveness analysis and benefit-cost analysis of interventions during early childhood development with both physical growth and cognition as key outcomes.